SELF-SERVICE BUSINESS INTELLIGENCE AS A DECISION-MAKING SUPPORT TO MINIMIZE STOCKOUT AT RY MART MINIMARKET - Rosyid, Yaqub Kasuma; Andi Purnomo, Muhammad Ridwan (International Journal of Multidisciplinary Research and Literature, 2025)
Some of the problems found in this study include : (1) Stockout happens at RY Mart 1 and RY Mart 2 (2) Inappropriate decision-making because it is not based on data and in-depth analysis. This study aims to minimize stockout based on data and in-depth analysis using Self Service business intelligence at RY Mart. The research method used in this study is Nine Step Kimbal with Online Analytical Processing (OLAP). The data obtained from 2023-2025 transaction record of RY Mart 1 and RY Mart 2. The result of this study is Stockout Dashboard and order planning for RY Mart. The Dashboard shows that the amount of stockout influenced by the increase of sales because of holiday and demography around the mart. Only in RY Mart 1 stockout of Ice Cream happens and the amount of Cigarette and Beverage stockout is greater at RY Mart 2 than RY Mart 1. Safety Stock, Minimum stock, and Minimum Order Quantity are calculated to minimize the stockout.